Analisis Peran dan Tanggung Jawab Negara Indonesia Dalam Mengatasi Pelanggaran Hak Asasi Manusia Pada Pekerja Migran Indonesia - Bukit, Liametami Benedicta; Amina, Frahnaz (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Republic of Indonesia is obliged to play a role and be responsible for the security, comfort, safety, and welfare of Indonesian workers working abroad. However, the form of legal protection efforts implemented by the Indonesian government has not been optimal in its implementation. Human rights violations, including forced labor, human trafficking, abuse, and violence, are rampant among Indonesian citizens working abroad. This is due to the absence of clear legal protection. The research method used is normative legal research. The results of the study indicate that the Republic of Indonesia is obliged to be responsible for protecting migrant workers from placement to protection during the placement and post-placement period, as well as the role of the central and regional governments in providing advice, training, and coordination with related agencies. The rampant human rights violations against Indonesian migrant workers are due to the lack of coordination between related agencies, the imbalance of power between migrant workers and their employers, and the minimal access of migrant workers to information and legal assistance. Therefore, it is necessary to improve coordination with the destination countries of migration by the Ministry of Foreign Affairs, supervision of agents and recruiters by the Ministry of Manpower and Transmigration, and the active role of the National Human Rights Commission in handling cases of violations of migrant workers' rights and facilitating access to reporting.